Authorial Presence of Indonesian Authors in Academic Discourse: A Study of English and Indonesian Research Articles - Tsaqifa, Tsabita Intan; Roselani, Ni Gusti Ayu (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
This study scrutinizes the authorial presence in English and Indonesian research articles written by Indonesian authors. The study aims to identify the frequency of first-person pronouns used as a form of authorial presence across research articles. Furthermore, the study also intends to examine the discourse functions of these first-person pronouns in academic writing. A corpus of 168,122 words was analyzed by utilizing corpus linguistics methodology. The findings show that there is a difference in the use of first-person pronouns between the English and Indonesian sub-corpora with the most frequent usage of first-person pronouns found in English research articles. In addition, the study investigated the clusivity and the discourse functions of first-person pronouns within the research articles in both English and Indonesian. The results indicate that Indonesian authors tend to adopt the Western academic style in using first-person pronouns as authorial presence despite the conservative style used in their native language. This reflects the different norms of academic discourse across languages.